Effects of the Ni-Fe support microstructure on the electrochemical performance of the metal-supported solid oxide fuel cell - Zheng Dao Jin; Mohammed Kamal Warshi; Hee Jung Park (Journal of Asian Ceramic Societies)
Metal-supported solid oxide fuel cells are gaining attention for their economic advantages, robust mechanical properties, and resilience to thermal cycling. However, gas transport may be impeded by the dense and irregular microstructure of the metal support, which would reduce electrochemical efficiency. To address this challenge, polymethylmethacrylate, a pore-forming agent that can offer porosity and uniform pore distribution, has been employed in this study. Ni-Fe metal supports with a uniform microstructure have been successfully fabricated by adding the pore former. The porosity of the supports is controlled by varying the amount (0–15 wt%) of the pore former. The electrochemical performance of the Ni-Fe supported solid oxide fuel cells has been then examined. As a result, the highest power density has been achieved in the most porous cell (15 wt%), showing that the more porous the metal support, the better the electrochemical performance.